2014
DOI: 10.1124/mol.114.095141
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Hedgehog Signaling in Fibrosis

Abstract: The Hedgehog (Hh) signaling pathway plays a key role during embryogenesis and tissue regeneration. Recently, studies revealed that overactivated Hh signaling leads to fibrogenesis in many types of tissues. The activation of Hh signaling is involved in the epithelialmesenchymal transition and excessive extracellular matrix deposition. Blockade of Hh signaling abolishes the induction of the epithelial-mesenchymal transition and ameliorates tissue fibrosis. Therefore, new therapeutic targets to alleviate fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 139 publications
3
61
0
2
Order By: Relevance
“…For example, Jung et al (2015) reported that SHH pathway activation was observed, especially in the cholangiocytes of the peribiliary glands, in human patients with biliary atresia. In pathological studies, some have reported that Hh expression is considerably increased in fibrotic damaged biliary diseases in response to injury (Omenetti et al, 2008;Omenetti and Diehl, 2011;Cui et al, 2013;Hu et al, 2015). It has also been speculated that the SHH signaling pathway regulates the epithelial-mesenchymal transition of cholangiocytes (Omenetti et al, 2008;Jung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jung et al (2015) reported that SHH pathway activation was observed, especially in the cholangiocytes of the peribiliary glands, in human patients with biliary atresia. In pathological studies, some have reported that Hh expression is considerably increased in fibrotic damaged biliary diseases in response to injury (Omenetti et al, 2008;Omenetti and Diehl, 2011;Cui et al, 2013;Hu et al, 2015). It has also been speculated that the SHH signaling pathway regulates the epithelial-mesenchymal transition of cholangiocytes (Omenetti et al, 2008;Jung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gli proteins are transcription factors that belong to the Kruppel-like family and contain a zinc-finger DNA-binding domain (Hu et al, 2015). Mammals have 3 Gli proteins: Gli-1, Gli-2 and Gli-3.…”
Section: The Hedgehog Signaling Pathwaymentioning
confidence: 99%
“…88,89 They will proliferate, migrate, and secrete ECM proteins, thus leading to pancreatic fibrosis. 90,91 Fibrogenesis will appear approximately during the onset of a lesion. Hedgehog signaling induces progressive pancreatic fibrosis intermingled with proliferating ductal structures that are accompanied by the destruction of acinar structures.…”
Section: Introductionmentioning
confidence: 99%